The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/access.2022.3185124
|View full text |Cite
|
Sign up to set email alerts
|

Interference Suppression Using Deep Learning: Current Approaches and Open Challenges

Abstract: In light of the finite nature of the wireless spectrum and the increasing demand for spectrum use arising from recent technological breakthroughs in wireless communication, the problem of interference continues to persist. Despite recent advancements in resolving interference issues, interference still presents a difficult challenge to effective usage of the spectrum. This is partly due to the rise in the use of license-free and managed shared bands as well as other opportunistic spectrum access solutions. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…Guo et al [25] As observed in previous work on the application of CNNs on complete OPGs for age estimation [27,28], one often overlooked aspect is optimizing the neural network training setup, specifically the hyperparameter optimization process. In deep learning practice, this process usually requires a deep understanding of the training methods, along with an empirical approach, and directly impacts the model performance [29,30]. Furthermore, the effect of the chosen neural network model architecture, while starting to become prominent in literature, can benefit from a more in-depth investigation.…”
Section: Related Workmentioning
confidence: 99%
“…Guo et al [25] As observed in previous work on the application of CNNs on complete OPGs for age estimation [27,28], one often overlooked aspect is optimizing the neural network training setup, specifically the hyperparameter optimization process. In deep learning practice, this process usually requires a deep understanding of the training methods, along with an empirical approach, and directly impacts the model performance [29,30]. Furthermore, the effect of the chosen neural network model architecture, while starting to become prominent in literature, can benefit from a more in-depth investigation.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, researchers have turned to deep learning techniques to reduce the need for domain expertise [3], [5], [6]. Interference suppression applications have also widely used deep learning [7].…”
Section: Introductionmentioning
confidence: 99%